Repeating an Obligatory Prayer when One Finds a Congregation in the Mosque - Sri Ujiana Putri; Andi Indra Puteri; Khusnul Khotimah; Hilyah, Hilyah (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2025)
In everyday Muslim devotional life, it is not uncommon for an individual who has already performed an obligatory (farḍ) prayer—either privately or elsewhere—to arrive at a mosque where congregational prayer (ṣalāt al-jamāʿah) is being established. This situation raises a recurring jurisprudential question: should the individual repeat the obligatory prayer with the congregation, and what is the legal status (ḥukm) of such repetition (iʿādah)? This article aims to conceptualize the practice of repeating an obligatory prayer upon encountering a congregation and to examine the legal rulings and juristic reasoning surrounding it across the major Sunni schools of law. The study employs a qualitative, library-based methodology using a normative juridical approach, drawing on classical and contemporary works of fiqh, uṣūl al-fiqh, and ḥadīth. A comparative analysis is conducted of the positions held by the Ḥanafī, Mālikī, Shāfiʿī, and Ḥanbalī schools. The findings reveal that repeating an obligatory prayer with a congregation after having already fulfilled it—either individually or in another congregation—is generally regarded as a recommended (mandūb or sunnah) act rather than a renewed obligation. The repeated prayer is typically classified as supererogatory (nāfilah) or confirmatory in nature, intended to attain the additional merit of congregational worship, while the initial prayer remains the one that fulfills the legal obligation. Nevertheless, juristic disagreement persists regarding specific details, including the permissibility of repeating certain prayers such as ʿAṣr and Maghrib, as well as the ruling on repetition for those who have already prayed in congregation. By clarifying these differences and their evidentiary bases, this study provides a clearer jurisprudential framework for contemporary mosque communities and fiqh educators in addressing the practice of iʿādah of obligatory prayer.